TOWARD A HISTORY OF CHILEAN WRITTEN CULTURE. HAPPENINGS OF THE ALONSO DE ERCILLA’S BOOK, LA ARAUCANA. - Biotti Silva, Ariadna (Revista de Historia Social y de las Mentalidades, 2011)
The main objective of this paper is to present the first questioning about a history of the circulation of the book La Araucana, printed for the first time in 1569 and subsequently reprinted in various opportunities. Its central question implies a definition: What kind of historiography we can build considering the continuance, the force and the authority of a work that is still respected as a founding inheritance, and backbone of Chilean society? The paradigmatic center of this investigation resides in realizing the questions that emerge from the first chilean edition of the text published in Santiago in the year 1888.
Keywords: The History of the Book; The History of Reading; The History of Edition; La Araucana; Ercilla